Physical activity and associated factors in homosexual men - Fabiano Teixeira; Fabiana Sperandio; Fernando Cardoso (Revista Brasileira de Atividade Física e Saúde)
This study aimed to estimate the proportion of physically active men proportion of physically active men and investigate what factors may be associated with physical activity in men with bisexual and homosexual orientation. Six hundred and forty six men participated in the study, of whom 571 (88.4%) were homosexual and 75 (11.6%) were bisexual. A self-administered questionnaire was used to collect information on current age, age at first sex, body mass index (BMI), education level, marital status, perception of body image, gender orientation, and sexual orientation. Analyses used descriptive statistics and logistic regression, with the significance level set at 5%. Among homosexuals, physical activity was associated with masculine orientation, level of education, and dissatisfaction with body image due to being overweight. Physically active homosexuals were 9.93 times more likely to perceive themselves as masculine, 5.29 times more likely to have lower literacy levels, and 4.71 times more likely to have a partner. In conclusion, we found that homosexual men were physically active, dissatisfied with their body image, had a masculine orientation, and were in the normal weight range. This study may increase participants' awareness of the need for a healthy, physically active lifestyle.